2009
DOI: 10.1302/0301-620x.91b11.22486
|View full text |Cite
|
Sign up to set email alerts
|

The ‘pulseless pink’ hand after supracondylar fracture of the humerus in children

Abstract: We compared two management strategies for the perfused but pulseless hand after stabilisation of a Gartland type III supracondylar fracture. We identified 19 patients, of whom 11 were treated conservatively after closed reduction (group 1). Four required secondary exploration, of whom three had median and/or anterior interosseus nerve palsy at presentation. All four were found to have tethering or entrapment of both nerve and vessel at the fracture site. Only two regained patency of the brachial artery, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 16 publications
3
60
1
4
Order By: Relevance
“…Postoperative palsy of the median and ulnar nerve is common and may exceed 10% in Gartland type III fractures [20]. Since most of these injuries occur due to traction of the nerve during the dislocation, most lesions are neurapraxias and usually recover spontaneously within approximately 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative palsy of the median and ulnar nerve is common and may exceed 10% in Gartland type III fractures [20]. Since most of these injuries occur due to traction of the nerve during the dislocation, most lesions are neurapraxias and usually recover spontaneously within approximately 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of these injuries occur due to traction of the nerve during the dislocation, most lesions are neurapraxias and usually recover spontaneously within approximately 8 weeks. If these lesions are associated with a vascular compromise, entrapment of nerves and arteries is more likely and early revision should be considered [20,21]. Lesions to the radial nerve are a completely different issue in supracondylar fractures because this nerve is less likely to suffer traction injuries during dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…It is not an emergency if the hand remains perfused [7]. However, controversy exists on whether or not to explore the artery if the pulse is absent but the hand remains perfused after reduction and stabilisation of the fracture [8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have noted the association between neurologic deficit and vascular injury in these fractures, and the absence of return of median nerve function in the forearm and hand after CRPP may be an indication for surgical exploration. 22,27 Longterm follow-up studies of patients who required revascularization has shown that growth and function are good but did note some aneurysmal change in those patients who had required vein grafting. Periodic follow-up with ultrasound to evaluate those patients with reversed vein grafts in the antecubital fossa has been proposed.…”
Section: Other Causes Of Closed Arterial Damagementioning
confidence: 99%